Implementation of Employee Mapping in the Regional Apparatus of the Buleleng Regency Government - I Made Nindya Hutama; Putu Indah Rahmawati; I Nengah Suarmanayasa (Budapest International Research and Critics University, 2022)
In the structure of regional apparatus, there are individuals who play an important role in achieving organizational goals who fill critical position formations in the organization, but sometimes not all critical position formations in regional apparatus are filled which have an impact on the implementation of the duties and functions of regional apparatus. Employee mapping as one of the stages in talent management also contributes to the achievement of talent management goals. This study aims to analyze the implementation of employee mapping, identify obstacles in the implementation of employee mapping, and formulate strategies for implementing employee mapping in relation to employee career development in regional apparatus within the Buleleng Regency Government. This type of research is descriptive qualitative research, data collection is carried out by semi-structured interviews with selected (purposive) informants in regional apparatus whose critical position formations are not fully filled, field observations and secondary data collection from documents related to staffing in regional apparatus. Data analysis was carried out using the Miles and Huberman data reduction method. The research formulates a strategy for implementing employee mapping which consists of providing regional regulations governing the implementation of talent management, providing facilities for competency testing and employee assessment, as well as optimizing the personnel information system.